2016
DOI: 10.1038/nm.4071
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the understanding of autism disease mechanisms through genetics

Abstract: Progress in understanding the genetic etiology of autism spectrum disorders (ASD) has fueled remarkable advances in our understanding of its potential neurobiological mechanisms. Yet, at the same time, these findings highlight extraordinary causal diversity and complexity at many levels ranging from molecules to circuits and emphasize the gaps in our current knowledge. Here we review current understanding of the genetic architecture of ASD and integrate genetic evidence, neuropathology and studies in model sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
620
1
18

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 726 publications
(646 citation statements)
references
References 300 publications
(304 reference statements)
7
620
1
18
Order By: Relevance
“…The highly polygenic nature of ASD (3)(4)(5) suggests that the analysis of the full spectrum of sequence variants in hundreds of genes will be necessary for deeper understanding of disrupted neuronal function. Prioritization of ASD risk genes initially focused on known pathways with recognized relevance to pathogenesis of ASD, such as synaptic function and neuronal development (6).…”
mentioning
confidence: 99%
“…The highly polygenic nature of ASD (3)(4)(5) suggests that the analysis of the full spectrum of sequence variants in hundreds of genes will be necessary for deeper understanding of disrupted neuronal function. Prioritization of ASD risk genes initially focused on known pathways with recognized relevance to pathogenesis of ASD, such as synaptic function and neuronal development (6).…”
mentioning
confidence: 99%
“…The interface of human genetics and neuroscience has typically focused on rare, highly penetrant variants that permit generation of transgenic animals with a robust phenotype 5,[31][32][33][34] . Neuroscientists now face the challenge of obtaining biological insights through investigation of the multiple weakly penetrant variants, identified through modern genomics, that act through unknown neurological mechanisms, in a manner highly dependent on genetic background 35 .…”
Section: Implications For Neuroscientistsmentioning
confidence: 99%
“…Early twin and family studies have shown that ASD is highly heritable [15], suggesting a strong genetic predisposition. In addition to inherited mutations, recent advances in genetics and genomics have identified a large number of de novo copy-number variations and singlebase-pair mutations in ASD patients, increasing the estimated proportion of patients with identifiable genetic mutations to 20%-40% [15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…In addition to inherited mutations, recent advances in genetics and genomics have identified a large number of de novo copy-number variations and singlebase-pair mutations in ASD patients, increasing the estimated proportion of patients with identifiable genetic mutations to 20%-40% [15][16][17][18][19][20]. As many ASD genes are known to regulate brain development and/or synapse function, theories of ASD relating to synaptic dysfunction, including excitatory/inhibitory imbalance and dysfunctional feedback regulation have been proposed [15,[21][22][23][24]. Since deficits in social behavior are hallmarks of ASD, molecules and circuits underlying social behavior have received special attention [25,26].…”
mentioning
confidence: 99%
See 1 more Smart Citation